Prognostic value of angiopoietin-2 in non-small cell lung cancer patients: a meta-analysis - Xuan, Zi-Xue (World J Surg Oncol, 2016)
BACKGROUND: Non-small cell lung cancer (NSCLC) is the most frequent cause of cancer deaths worldwide. The targeted therapy had made important progress in recent years, but few potential predictive biomarkers for prognosis of NSCLC patients were identified. Angiopoietin-2 (Ang-2), a cytokine upregulated in tumor endothelial cells and some tumor cells including NSCLC, is a partial agonist and antagonist of angiopoietin-1 (Ang-1). Ang-1 is another ligand for the tyrosine kinase receptor Tie2; it promotes recruitment of pericytes and smooth muscle cells, stabilizing vascular networks by binding to Tie2. Although many studies mainly considered that Ang-2 correlated with progression and prognosis of NSCLC significantly, there are much conflicting and controversial data. Therefore, we conducted a meta-analysis to assess the relationship between Ang-2 and prognosis, a clinical outcome of NSCLC. METHODS: The search was based on major databases from PubMed, Cochrane Library, EMBASE, and CNKI, and 20 eligible publications (range from 2002 to 2015) are included in our meta-analysis with 2011 NSCLC patients in total. These studies illuminated the correlation between the expression of Ang-2 and NSCLC, based on either prognostic factors or clinicopathological features. Pooled calculations were carried out on the odds ratio (OR) and the corresponding 95 % confidence interval (CI) to perform this meta-analysis, and all statistical analyses were carried out by STATA 12.0 and Review Manager 5.3. RESULTS: According to our results, the expression of Ang-2 in NSCLC tissues was significantly higher than that in normal lung tissues, indicating that Ang-2 over-expression may be a predictive marker (pooled OR = 5.09, corresponding 95 % confidence interval (95 % CI) 3.10–8.36, p = 0.000). In addition, our pooled data showed that Ang-2 expression was positively correlated with tumor stages (pooled OR = 3.58, 95 % CI 2.40–5.35, p = 0.000), differentiation (pooled OR = 0.65, 95 % CI 0.45–0.94, p = 0.02), lymphatic invasion (pooled OR = 3.15, 95 % CI 1.97–5.03, p = 0.000), and poor survival (pooled OR = 1.93, 95 % CI 1.47–2.52, p = 0.000) of NSCLC, but seems to have no significant impact on tumor size (pooled OR = 1.09, 95 % CI 0.59–2.00, p = 0.78). CONCLUSIONS: These results demonstrate that Ang-2 expression significantly correlated with poor prognosis for patients with NSCLC.